Clinical Teaching of Residents in Operating Room: A Review of Methods and Strategies for Strengthening Teaching and Learning - Majid Shirani; Masoumeh Rahimi (Kerman University of Medical Sciences, 2018)
Background The operating room is considered a learning platform for technical and non-technical skill training. Training in operating rooms helps learners from different groups, especially surgery residents, acquire the necessary clinical competence. Nevertheless, operating room training is only effective if it is accompanied by efficient and applicable teaching methods. Objectives The current study aimed at reviewing the strategies and methods to enhance teaching and learning of residents in operating room settings. Methods The current review study was conducted based on library studies and review of the literature. PubMed, SID, and MagIran databases, as well as Google Scholar search engine, were searched using relevant phrases and keywords. A total of 60 articles were retrieved, out of which 22 articles were identified as consistent with the study objectives. Results The data obtained from the literature review were categorized into three sections: "General structure of training in the operating room", "strategies and methods to strengthen teaching and learning in the operating room", and "structured training models in the operating room". Finally, application of these strategies in clinical teaching was summarized in three stages: Before operation, during operation, and after operation. Conclusions The operating room is a clinical facility with specific characteristics, which can challenge teaching in this setting. However, application of effective strategies and methods, as well as efficiently structured training based on the proposed models can facilitate teaching and learning enhancement in operating rooms.